Oil Industry Training for Indigenous People : The Bolivian Experience - World Bank (Washington, DC, 2014)
Bolivia has the highest percentage of indigenous peoples in America and has recently attracted substantial investments in gas pipelines and in exploration work in new areas. the country also has one of the most dynamic indigenous peoples movement in the region. The joint UNDP/World Bank ESMAP program designed a pilot training program to instruct indigenous peoples on the impact of hydrocarbon activities. The pilot training program in Bolivia was sufficiently successful to warrant publication of this report. The report is organized as follows: After the Introduction, Chapter 2 describes the program's background. It addresses the development of the oil and gas industry in Bolivia, the specific demands of indigenous peoples in this respect, the progress made with the relevant legislation, and the circumstances under which this training program was designed. Chapter 3 describes the experience of program implementation, which was split into three phases: a preparatory phase, a development (training) phase, and a dissemination phase. Chapter 4 includes the lessons, recommendations, and future steps envisaged as a result of the experience. Annex A describes the Population, Energy and Environmental Prpgram; Annex B contains the text of the proposed regulations governing hydrocarbon activities in the indigenous people's communal territories.